Feedback stabilization for a bilinear control system under weak observability inequalities. (March 2020) - Ammari, Kaïs; Ouzahra, Mohamed
Abstract: In this paper, we discuss the feedback stabilization of bilinear systems under weak observation properties. In this case, the uniform stability is not guaranteed. Thus we provide an explicit weak decay rate for all regular initial data. Applications to Schrödinger and wave equations are provided.